Corneal confocal microscopic characteristics of acute angle-closure crisis - Weiwei Wang; Xin Yang; Qian Yao; Qianqian Xu; Wenting Liu; Jianrong Liu (BMC Ophthalmology, 2022)
Abstract Background To investigate characteristics of the acute angle-closure crisis (AACC) and fellow eyes using confocal microscopy. Methods Unilateral AACC patients hospitalized at the Xi’an People’s Hospital from October 2017 to October 2020 were recruited in this cross-sectional study. Age-matched participants scheduled for cataract surgery were enrolled as a healthy control group. Corneal epithelial cells, subepithelial nerve fiber plexus, stromal cells, and endothelial cells were examined by confocal and specular microscopy. Results This study enrolled 41 unilateral AACC patients (82 eyes) and 20 healthy controls (40 eyes). Confocal microscopy revealed that the corneal nerve fiber density, corneal nerve branch density and corneal nerve fiber length were reduced significantly in AACC eyes. The stromal cells were swollen and the size of the endothelial cells was uneven with the deposition of punctate high-reflective keratic precipitate on the surface. In severe cases, the cell volume was enlarged, deformed, and fused. The corneal subepithelial nerve fiber, stromal layer, and endothelial layer were unremarkable in the fellow eyes, and the density of the endothelial cells was 2601 ± 529 cells/mm2, which was higher than 1654 ± 999 cells/mm2 in AACC eyes (P < 0.001). Corneal edema prevented the examination of 17 eyes using specular microscopy and in only four eyes using confocal microscopy. There were no significant differences in endothelial cell density between confocal and specular microscopy in the AACC eyes (P = 0.674) and fellow eyes (P = 0.247). The hexagonal cell ratio reduced significantly (P < 0.001), and average cell size and coefficient of variation of the endothelial cells increased significantly compared with fellow eyes (P < 0.001, P = 0.008). Conclusions AACC eye showed decreased density and length of corneal subepithelial nerve fiber plexus, activation of stromal cells, increased endothelial cell polymorphism, and decreased density.